2014
DOI: 10.1149/2.0501503jes
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of 1-Amino-4-Hydroxy-9,10-Anthraquinone Governs Its Electrochemical Behavior in Non-Aqueous and Aqueous Media: A Cyclic Voltammetry Study

Abstract: The electrochemical behavior of 1-amino-4-hydroxy-9,10-anthraquinone (1-AHAQ) was studied in acetonitrile, dimethyl formamide and dimethyl sulfoxide. In such solvents 1-AHAQ undergoes successive two one-electron reduction forming semiquinone and quinone dianion respectively in which the first step is completely reversible and the second step is quasi-reversible. The reduction and oxidation potentials are dependent on the polarity of the media. The electrochemical parameters are evaluated and correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 72 publications
(154 reference statements)
2
27
0
Order By: Relevance
“…The electrochemical aspect of the molecule at physiological pH (7.4) is an important step for a molecule in determining its biological action. However, in earlier studies [32] , [33] the electrochemical reduction of 1-AHAQ was not studied in aqueous buffer at physiological pH (7.4) and that is the reason why in the present study we report the redox behavior of 1-AHAQ in aqueous solution at pH 7.4. This shows a quasireversible two-electron reduction at –665 mV corresponding to the reduction of quinone to quinone dianion [ Fig.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…The electrochemical aspect of the molecule at physiological pH (7.4) is an important step for a molecule in determining its biological action. However, in earlier studies [32] , [33] the electrochemical reduction of 1-AHAQ was not studied in aqueous buffer at physiological pH (7.4) and that is the reason why in the present study we report the redox behavior of 1-AHAQ in aqueous solution at pH 7.4. This shows a quasireversible two-electron reduction at –665 mV corresponding to the reduction of quinone to quinone dianion [ Fig.…”
Section: Resultsmentioning
confidence: 70%
“…In our very recent studies [32] , [33] we observed that 1-AHAQ undergoes single step quasi-reversible reduction by two electrons in aqueous media at neutral pH (7.0). The electrochemical aspect of the molecule at physiological pH (7.4) is an important step for a molecule in determining its biological action.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…While in an organic hydrophobic environment like DMSO, hydrogen of the secondary amine (-NH-) and one hydrogen of amino group (-NH 2 ) would prefer to form intramolecular hydrogen bonding. Another hydrogen of the amino group could form intermolecular hydrogen with negatively charged oxygen of the DMSO molecule [23]. Some possible structures of KN-R in aqueous solution and organic solvent are shown in Fig.…”
Section: Uv-spectrophotometry Study Of Dye-surfactant Interactionmentioning
confidence: 99%